2019
DOI: 10.18502/ijaai.v18i4.1418
|View full text |Cite
|
Sign up to set email alerts
|

Histologic, Metabolic, and Inflammatory Changes in the Liver of High-fat Diet-induced Obese Rats before and after Vitamin D Administration

Abstract: The current study aimed to investigate the effects of vitamin D administration on the markers of inflammation and metabolic damages in the liver of high-fat diet-induced obese rats. Forty male Wistar rats were divided into two groups of control receiving a normal diet (ND) and intervention receiving a high-fat diet (HFD). After 16 weeks, each group was divided into two groups including ND, ND + vitamin D, HFD, and HFD + vitamin D. Vitamin D was administered by oral gavage for five weeks at the dose of 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…The results of changes in food intake, body weight and serum vitamin D concentrations had been reported in our previous work (Hajiluian et al, 2017;Nameni et al, 2017;Yaghchiyan et al, 2019). Briefly, food intake in all of groups increased significantly until the administration of vitamin D, whereas after vitamin D administration, in ND and HFD groups, food intake decreased significantly (P < 0.001, Figure 1).…”
Section: Changes In Food Intake Body Weight and Serum Vitamin D Concentrationssupporting
confidence: 76%
See 1 more Smart Citation
“…The results of changes in food intake, body weight and serum vitamin D concentrations had been reported in our previous work (Hajiluian et al, 2017;Nameni et al, 2017;Yaghchiyan et al, 2019). Briefly, food intake in all of groups increased significantly until the administration of vitamin D, whereas after vitamin D administration, in ND and HFD groups, food intake decreased significantly (P < 0.001, Figure 1).…”
Section: Changes In Food Intake Body Weight and Serum Vitamin D Concentrationssupporting
confidence: 76%
“…The protocol of the study has been explained before (Hajiluian et al, 2017;Nameni et al, 2017;Yaghchiyan et al, 2019). A brief explanation of procedures and methods is as follows:…”
Section: Methodsmentioning
confidence: 99%
“…(Zhou et al, 2018) MCP1 can activate TGF-b production and increase the fibrogenic potential by stimulating TGF-b and collagen synthesis. (Yaghchiyan et al, 2019) Further, MCP-1 was recently reported to enhance TGF-b signaling via increasing expression of MMP-9. (Youn et al, 2019) The silence of NOX-2 in cardiomyocyte can attenuate hypoxia-induced oxidative stress and apoptosis indicating that NOX-2 may cause cardiac dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…It is also considered as a chronic low-grade infl ammatory disorder because there is an extreme production of pro-infl ammatory molecules in obese people [9]. The liver is most susceptible to these cytokines by causing liver damage [10]. Moreover, insulin resistance and type 2 diabetes are prone to develop in people who are obese.…”
Section: Discussionmentioning
confidence: 99%